Do Ugly Ducklings Become Gray Swans?. Issue 4 (31st March 2021) - Herber, John W.
Abstract: The Ugly Duckling fairy tale tells of an ugly duckling who grows into a beautiful swan. Many companies or plants have action items from many sources that are ugly. They have lingered a long time, they are poorly defined and/or they have little chances of being completed as written. This article explains steps to recognize action items that are ugly and what can be done to bring them to closure before they mature into a Gray Swan, an improbable, but still devastating event.